Implementation of Electric Vehicle Kit (EV-KIT) to Improve the Competence of Automotive Technology Vocational Education Students at Ahmad Dahlan University in Electric Vehicle Knowledge - Dwiky Febrianovic Sutarja; Bambang Sudarsono; Fanani Arief Ghozali (CV. Creative Tugu Pena, 2025)
The rapid development of electric vehicle (EV) technology has created an urgent need for vocational students to master the concepts and practical knowledge of electric power systems in automotive applications. However, the lack of appropriate learning media and limited access to real EV components have made it difficult for students to understand the relationship between theoretical knowledge and its practical application. This study aims to implement an Electric Vehicle Kit (EV-KIT) as an innovative learning medium to improve students’ understanding of electric vehicle components and working systems in the Pendidikan Vokasional Teknologi Otomotif (PVTO) Program at Universitas Ahmad Dahlan. The research used a Research and Development (R&D) approach with the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The product was validated by three experts and tested through two trials involving 6 students in a limited trial and 19 students in an expanded implementation. Data were collected using observation sheets, questionnaires, and pre-test and post-test instruments, then analyzed using descriptive statistics and a paired sample t-test. The validation results showed that the EV-KIT achieved a feasibility level of 88.4%, categorized as “very feasible.” The average N-Gain score of 0.65 indicated a moderate to high improvement in students’ knowledge of EV components and their functions. Furthermore, students’ responses reached 86.7%, categorized as “very good,” showing that the EV-KIT is practical, safe, and effective in supporting active and project-based learning. The implementation of EV-KIT not only improved students’ conceptual understanding but also enhanced their motivation and readiness to face the transition toward electric vehicle technology in the automotive industry. Therefore, the EV-KIT is recommended as an alternative instructional media for vocational and higher education to strengthen competence in electric vehicle systems.